2022
DOI: 10.3390/plants11202791
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chemical Composition of Miscanthus × giganteus Raised in Different Climate Regions in Russia

Abstract: Lignocellulosic biomass is of great interest as an alternative energy resource because it offers a range of merits. Miscanthus × giganteus is a lignocellulosic feedstock of special interest, as it combines a high biomass productivity with a low environmental impact, including CO2 emission control. The chemical composition of lignocellulose determines the application potential for efficient industrial processing. Here, we compiled a sample collection of Miscanthus × giganteus that had been cultivated in differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…In this study, Miscanthus × giganteus was used as the feedstock, having the following chemical compositions: 50.2 wt.% Kürschner cellulose, 19.5 wt.% acid-soluble lignin, 21.2 wt.% pentosans, 1.63 wt.% ash, and 0.5 wt.% extractives [ 53 ]. The quantitative determination methods for the feedstock components were similar to those used for cellulose components ( Section 2.2.1 ), except for the quantitative determination of Kürschner cellulose and extractives.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Miscanthus × giganteus was used as the feedstock, having the following chemical compositions: 50.2 wt.% Kürschner cellulose, 19.5 wt.% acid-soluble lignin, 21.2 wt.% pentosans, 1.63 wt.% ash, and 0.5 wt.% extractives [ 53 ]. The quantitative determination methods for the feedstock components were similar to those used for cellulose components ( Section 2.2.1 ), except for the quantitative determination of Kürschner cellulose and extractives.…”
Section: Methodsmentioning
confidence: 99%
“…The overview of the world literature on alternative cellulose sources has demonstrated that despite the diversity of Miscanthus species and their habitats [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ], as well as their wide applications ranging from paper industry to biosynthesis products [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the information on Miscanthus cellulose as the substrate for chemical functionalization into CN is presently quite limited, except for the authors’ single studies.…”
Section: Introductionmentioning
confidence: 99%
“…Compositional analyses of these accessions studied here were within ranges previously reported for M . × giganteus of 32.7%–52.9% for cellulose, 17.1%–33.8% for hemicellulose, and 7.6%–33% for lignin content, though there can be substantial variations due to the environment and harvest time (Gismatulina et al., 2022; Turner et al., 2021; Xu et al., 2020). Although there was some variation in compositional analyses among accessions in this study, variations were generally small, indicating that differences in theoretical ethanol yields are largely attributed to biomass yields rather than composition.…”
Section: Discussionmentioning
confidence: 99%
“…The essential merit of Miscanthus is its high cellulose content ranging from 36 to 55%, according to different data [ 12 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Moreover, the Miscanthus biomass contains valuable constituents, such as hemicelluloses and lignin ( Figure 2 ).…”
Section: Benefits Of Energy Crop Miscanthus As a T...mentioning
confidence: 99%
“…Miscanthus refers to cellulosic raw material resources, and its biomass contains about 50% cellulose [ 7 , 45 , 46 , 47 ]. Cellulose is the most valuable component of Miscanthus , and a global trend towards replacing wood cellulose by Miscanthus cellulose in the manufacture of cupboards, disposable tableware, and paper is currently being observed worldwide.…”
Section: Miscanthus In Pulp and Paper Industrymentioning
confidence: 99%